2012
DOI: 10.1007/s10787-011-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aqueous extract of Spinacia oleracea leaves in experimental paradigms of inflammatory bowel disease

Abstract: The present study was aimed to assess the protective effect of aqueous extract of Spinacia oleracea leaves (AESO 250, 500, and 1,000 mg/kg, p.o.) in inflammatory bowel disease using acetic acid- and ethanol-induced colitis in mice and indomethacin-induced enterocolitis in rats. The preliminary phytochemical analysis and further high performance thin layer chromatographic (HPTLC) analysis and phytochemical tests of HPTLC bands confirmed the presence of flavonoids and tannins in AESO. In acute oral toxicity stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…This result suggests that TA may be able to ameliorate inflammatory bowel disease (IBD), including Crohn’s disease, which is dependent on Th1 and Th17 immune responses ( Hill and Artis, 2010 ; Strober et al., 2002 ). Indeed, it has been reported that some foods containing TA may ameliorate colitis ( Orsi et al., 2014 ; Otari et al., 2012 ; Ritchie et al., 2017 ), but the role of TA in the anti-inflammatory properties of these foods has not been clearly addressed.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that TA may be able to ameliorate inflammatory bowel disease (IBD), including Crohn’s disease, which is dependent on Th1 and Th17 immune responses ( Hill and Artis, 2010 ; Strober et al., 2002 ). Indeed, it has been reported that some foods containing TA may ameliorate colitis ( Orsi et al., 2014 ; Otari et al., 2012 ; Ritchie et al., 2017 ), but the role of TA in the anti-inflammatory properties of these foods has not been clearly addressed.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of rubidium to potassium-deficient diets helps to avert the lesions characteristic of potassium reduction in rats [ 30 ]. It was observed that the aqueous extract of Spinacia oleracea eaves has protective effect, for example, attenuating the spread of lesions [ 31 ]. The presence of Rb in Spinacia oleracea substantiates the therapeutic usage of it against the development of lesions.…”
Section: Resultsmentioning
confidence: 99%
“…The protonated form of the acid liberates protons within the intracellular space, causing a massive intracellular acidification resulting in an immense epithelial damage. 45 The weight of the inflamed colonic tissue is considered as a reliable and sensitive indicator for the severity, extent of intestinal inflammation, over production of TNF α, IL-1β and IL-6 on intrarectal administration of acetic acid. 46,47,48,49 Consistent with this notion, the results of this study revealed, acetic acid treated rats was showed significant increase colon weight and macroscopic damage score, indicative of formation of ulcers, edema and increases inflammatory cytokines levels such as TNF α, IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%